Efficacy of Homoeopathic Remedy in the Treatment of Prolapse of third eyelid in street dog: A case report - Girishkumar Parmar (The Indian Veterinary Journal, 2026)
Prolapse of third eyelid is common disease among dog and in modern medical science there is only surgical treatment is available for treating such disease with high recurrence chances. Homoeopathy is very unique medical science which was discover by Dr Samuel Hahnemann in 1796 and this science have based on some basic concept for treatment of living organism that is similia similibus curantur. Homoeopathy (Overall, 2009).has very good affinity in case of animals’ especially surgical disease (Dugan,1992). One a case street dog was suffering from prolapse of third eye lid since 3 months. It was observed and given suitable homoeopathic medicine to this.dog (Raza, 2013).